Studi Komparasi Parameter Lingkungan Proses Produksi Garam di Indonesia - Fauziyah, Lailatul; Yulitasari, Fara’idhya Intan; Maulana, Ilham; Camila, Aysyah Fitria; Efendy, Makhfud; Nuzula, Nike Ika; Pratiwi, Wiwit Sri Werdi (Universitas Trunojoyo Madura, 2025)
Indonesia has great potential as a salt-producing country due to its extensive coastline and favorable geographical conditions. However, the quality and quantity of domestic salt production are still suboptimal and fail to meet the domestic industrial salt demand. This study aims to analyze and compare environmental parameters that influence the suitability of salt pond sites in several regions of Indonesia, as well as to understand the salt production process based on the deposition of impurities at various stages of crystallization. The study was conducted at eight locations with different climatological and hydrological characteristics, including rainfall, soil permeability and type, duration of sunlight, air humidity, wind speed, air temperature, evaporation rate, and water saturation. The results of the study indicate that environmental parameters play a role in determining the effectiveness and efficiency of the salt production process. Pati and Aceh Besar districts are classified as unsuitable (N) for soil parameters, thus requiring adaptive technologies such as geomembranes and boiling methods. The salt crystallization process begins with the flow of seawater from the bozem to the crystallization table, where impurities such as mud, sand, Fe₂O₃, CaCO₃, CaSO₄•2H₂O, and gypsum are gradually deposited. Meanwhile, NaCl deposits form on the crystallization table, and MgSO₄ and NaBr compounds are found in the bittern pond. This study emphasizes the importance of land suitability mapping based on environmental parameters to enhance national salt productivity and quality, as well as serving as a foundation for developing more adaptive salt production policies tailored to regional conditions.